Analysis of thermal comfort models of users of public urban and intercity transport - Yakovenko, Yevheniia; Voichyshyn, Yurii; Horbay, Orest (Видавництво Львівської політехніки, 2022)
Regardless of the vehicle's application, the thermal comfort of the vehicle's occupants and driver is given increased attention. Maintaining a sense of thermal comfort, whether for safety, health or occupant thermal well-being reasons, is one of the most important goals of heating, ventilation and air conditioning (HVAC) systems. There are a significant number of physical variables that affect thermal comfort. Therefore, evaluating thermal comfort has always been a complex issue and has attracted the attention of researchers. The feeling of thermal comfort is provided by factors that depend on the heat exchange between the human body and the external environment. It is well known that one of the requirements to be fulfilled is to find a person in thermal neutrality in the environment according to the comfort equation. The article describes and evaluates the following indicators: DTS (dynamic thermal sensitivity), TS (thermal sensitivity), PMV (predicted mean voice) and PPD (predicted percentage of dissatisfaction). The most common models for evaluating thermal comfort, namely the Predicted Mean Vote (PMV), Taniguchi’s model, Zhang’s model and Nilsson’s model in a variety of car cabin conditions, have been reviewed. The limitations of these models in terms of the objectivity of the results obtained are analysed.
Keywords: thermal comfort; vehicle; DTS; TS; PMV; PPD; thermal model; energy balance